A Review of the Updated Pharmacophore for the Alpha 5 GABA(A) Benzodiazepine Receptor Model. (10th November 2015) - Clayton, Terry; Poe, Michael M.; Rallapalli, Sundari; Biawat, Poonam; Savić, Miroslav M.; Rowlett, James K.; Gallos, George; Emala, Charles W.; Kaczorowski, Catherine C.; Stafford, Douglas C.; Arnold, Leggy A.; Cook, James M.
Abstract : An updated model of the GABA(A) benzodiazepine receptor pharmacophore of the α 5-BzR/GABA(A) subtype has been constructed prompted by the synthesis of subtype selective ligands in light of the recent developments in both ligand synthesis, behavioral studies, and molecular modeling studies of the binding site itself. A number of BzR/GABA(A) α 5 subtype selective compounds were synthesized, notably α 5-subtype selective inverse agonist PWZ-029 (1 ) which is active in enhancing cognition in both rodents and primates. In addition, a chiral positive allosteric modulator (PAM), SH-053-2′F-R-CH3 (2 ), has been shown to reverse the deleterious effects in the MAM-model of schizophrenia as well as alleviate constriction in airway smooth muscle. Presented here is an updated model of the pharmacophore for α 5 β 2 γ 2 Bz/GABA(A) receptors, including a rendering of PWZ-029 docked within the α 5-binding pocket showing specific interactions of the molecule with the receptor. Differences in the included volume as compared to α 1 β 2 γ 2, α 2 β 2 γ 2, and α 3 β 2 γ 2 will be illustrated for clarity. These new models enhance the ability to understand structural characteristics of ligands which act as agonists, antagonists, or inverse agonists at the Bz BS of GABA(A) receptors.